Efektivitas Gerakan Literacy Lodge dalam Meningkatkan Budaya Membaca Siswa - Katili, Fadillah V.N.; Halidu, Salma; Katili, Sukri (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
The lack of public interest in reading, whether students, workers or non-workers, shows that the reading culture in Indonesia is still very lacking. This research aims to explore and analyze the effectiveness of the Literacy Lodge movement in improving the culture of reading literacy among the community. The research method used is descriptive qualitative, with data collection through interviews, observation, questionnaires and document analysis. The research results show that the Literacy Lodge has succeeded in increasing participants' interest in reading, expanding access to reading materials, and creating an environment that supports literacy activities. The structured and interactive activities at the Literacy Lodge build an active and vibrant community of readers, significantly positively impacting individual and group reading habits. It is hoped that these findings will provide insight into the development of similar literacy movements in various regions and support efforts to improve literacy culture in general.